PEMIKIRAN ARISTOTELES TENTANG KEWARGANEGARAAN DAN KONSTITUSI - Winarno, Winarno (HUMANIKA, 2015)
Citizenship includes elements of identity, participation, rights, obligations, and acceptance of shared social values. Aristotle, the ancient Greek thinker states that citizenship is a form of citizen participation in public life. Good citizens are those engaged in public life better while being ruled and governed. Citizenship can not be separated from the concept of the constitution. Determining who is a citizen based on the state constitution. There is a "Wrong Constitutions", which includes Tirany, Oligarchy and Democracy and the "Right Constitutions", covers Kingship, Aristocracy and Polity or Constitutional Government. The Constitution is important for a country as long as it is intended for the public good and reach a sense of justice.